Climate-smart irrigation planning for rabi maize (Zea mays L.): CMIP6 multi-model projections in north-central Bangladesh - Md Touhidul Islam; Deboneel Kundu Partho; Nusrat Jahan; Md Tarek Abrar; Azizul Hakim; Md Mazharul Islam; Md Touhidul Haider; A.K.M. Adham (Journal of Agriculture and Food Research, 2025)
Climate change poses significant challenges to agricultural water management in Bangladesh, particularly for dry-season rabi maize cultivation. This study projected irrigation water requirements for maize in Mymensingh, north-central Bangladesh, under future climate scenarios. Using five CMIP6 models (BCC-CSM2-MR, CMCC-ESM2, MIROC6, CNRM-CM6-1, EC-Earth3-Veg-LR) across four emission pathways (SSP1-2.6, SSP2-4.5, SSP3-7.0, SSP5-8.5), we simulated climate conditions for three-time horizons: short-term (ST, 2026–2050), mid-term (MT, 2051–2075), and long-term (LT, 2076–2100). The CROPWAT model integrated these projections with soil and crop parameters to determine water requirements and develop irrigation schedules. Results revealed progressive increases in potential crop water requirements of 4.05–5.88 % (ST), 6.37–9.47 % (MT), and 8.11–15.06 % (LT). Potential irrigation requirements intensified by 13.55–15.56 %, 16.73–18.94 %, and 13.39–26.02 % across respective timeframes. Temperature emerged as the dominant driver, with January minimum temperatures projected to rise by 1.01–4.50 °C by 2076–2100. Effective rainfall showed substantial decreases (6.83–25.38 %) across scenarios, creating compound pressure on irrigation systems. Irrigation schedules shifted toward earlier final irrigation events under higher emission scenarios, reflecting accelerated crop development under warming conditions. Model performance evaluation revealed stronger simulation capabilities for temperature variables (NSE: 0.886–0.947) than precipitation (NSE: 0.738–0.828). Sensitivity analysis revealed that temperature-driven changes accounted for 10.57–24.05 % of increased irrigation demand in LT projection, while soil moisture reduction scenarios (10–20 %) showed impacts comparable to climate change projections, highlighting soil degradation risks. These findings emphasize the need for climate-adaptive irrigation strategies, including precision technologies, improved water use efficiency, heat-tolerant varieties, and conservation agriculture practices to ensure sustainable maize production in Bangladesh's changing climate.